Application-assisted Project Based Learning Transformation During Covid-19 Adaptation at Madrasah Aliyah Negeri - Jubelando O Tambunan; Elsida Aritonang (Sean Institute, 2022)
One learning model that is regulated by Covid-19 during online learning is Project-Based Learning (PBL). Prior to the pandemic, Madrasah Aliyah Negeri (MAN) Dairi had begun the Project-Based Learning method, although at the time, it relied solely on digital technology for communication. Although online learning has been implemented, it cannot be optimized because the only platform available is Whatsapp for communication. With the school environment and strategic location in the capital city of the Dairi Regency, integrated learning should be implemented, particularly in Project-Based Learning, to maximize adaptation to this new habit. Researchers are therefore interested in developing a platform that can support and transform Project-Based Learning learning model. The method utilized for system development is the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). The results of this study reveal a platform that can accommodate teachers and students in the use of Project-Based Learning (PBL), with 80.22 percent of the responses falling into the